Games in favor of well-being: The impacts of electronic games on the individual (Research, Society and Development, 2025)
Electronic games are already widespread in today's habits and culture, although they are still often stigmatized. This study investigates the impact of electronic games on the individual and their possible uses within the area of Health, through a bibliographical review that brings together academic and documentary sources. The aim is to identify the facts and inconclusions present in the literature related to the effects of electronic games and their possible uses as tools that promote the health, development and well-being of individuals. The research adopts the narrative literature review method, with an emphasis on qualitative aspects, in order to explore the topic in a broader and more flexible way. The results show that electronic games go beyond entertainment and can promote social interactions and stimulate learning and cognitive development. However, the literature still lacks research with methodologies that enable direct comparisons between results. The conclusion is that although there is still controversy in the literature, electronic games are a strong tool for individual development and interventions in a variety of contexts, as long as they are used responsibly, with awareness and balance.